ChemInform Abstract: The New Alkali Cyclotrisilicate Cs8[Si6O16]. Issue 17 (4th April 2013) - Hlukhyy, Viktor; Faessler, Thomas F.
Abstract Hygroscopic transparent single crystals of Cs8[Si6O16] are obtained by high‐temperature reaction of Cs, Si, WO3, and HgO in the molar ratio of 5:5:1:1 (sealed Nb crucible in a fused silica tube, 1.